Virtual Nurse for Detecting Suicide Risk Behaviors in Adolescents - Yohanes Tarigan (Babali Nursing Research)
Introduction: Suicide is a complex phenomenon that is intriguing to study because its causes are still not fully understood. This phenomenon often garners media attention, as the number of incidents has significantly increased. Suicidal ideation frequently occurs in teenagers, and many who seek consultation report similar thoughts or engage in self-harm. The approach to problem-solving proposed in this research is the use of a virtual nurse as an early detection service for suicide risk behavior. A Virtual Nurse is an artificial intelligence-based application or system designed to provide health services and psychological support, particularly for teenagers. The Virtual Nurse uses machine learning algorithms to analyze user behavior, speech patterns, and interactions to identify signs of suicide risk. This study aims to analyze the effectiveness of the Virtual Nurse in detecting suicide risk behavior in adolescents.